PENDAMPINGAN PERENCANAAN PEMBELAJARAN BERBASIS PLATFORM DIGITAL PADA GURU-GURU DI SDN 107398 SEI ROTAN DAN SDN 104239 LENGAU SEPRANG - Nurmayani; Halimatussakdiah; Marisanta, Rani; Maulana Siregar, Waliyul (JS (JURNAL SEKOLAH), 2025)
Abstract: Mentoring in lesson planning using digital platforms plays a crucial role in improving the quality of education, particularly by supporting teachers in integrating technology into the learning process. This study aims to enhance teachers' pedagogical competence in designing digital-based lesson plans. The research method consists of four main stages: preparation, implementation, monitoring and evaluation, and follow-up. The study population includes teachers from SDN 107398 Sei Rotan and SDN 104239 Lengau Seprang, with a sample of 25 teachers. Data were collected through observations, interviews, and document analysis before and after the mentoring program. The results indicate a significant improvement in teachers' abilities, with lesson planning scores increasing from 51% to 82%. Teachers have become more proficient in integrating technology into the teaching process, utilizing platforms such as Canva, Kahoot, and Wordwall to create more interactive learning experiences. Thus, the digital-based mentoring program has proven effective in enhancing teachers' professional competence, motivating them to continue innovating, and encouraging the adoption of more creative and dynamic teaching strategies. Keyword: Mentoring; Lesson Planning; Teachers; Digital Platform. Abstrak: Pendampingan dalam perencanaan pembelajaran berbasis platform digital memiliki peran krusial dalam meningkatkan kualitas pendidikan, terutama dalam membantu guru mengadaptasi teknologi dalam proses pembelajaran. Penelitian ini bertujuan untuk meningkatkan kompetensi pedagogik guru dalam merancang pembelajaran berbasis digital. Metode yang digunakan mencakup empat tahapan utama: persiapan, pelaksanaan, monitoring dan evaluasi, serta tindak lanjut. Populasi penelitian meliputi guru di SDN 107398 Sei Rotan dan SDN 104239 Lengau Seprang, dengan sampel sebanyak 25 guru. Data dikumpulkan melalui observasi, wawancara, serta analisis dokumen sebelum dan sesudah pendampingan. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam kemampuan guru, dengan hasil perencanaan pembelajaran meningkat dari 51% menjadi 82%. Guru menjadi lebih terampil dalam mengintegrasikan teknologi dalam proses pembelajaran, seperti penggunaan Canva, Kahoot, dan Wordwall untuk menciptakan pengalaman belajar yang lebih interaktif. Dengan demikian program pendampingan berbasis digital terbukti efektif dalam meningkatkan kompetensi profesional guru, memotivasi mereka untuk terus berinovasi, serta mendorong penerapan strategi pembelajaran yang lebih kreatif dan dinamis. Kata Kunci: Pendampingan; Perencanaan Pembelajaran; Guru; Platform Digital.